2017
DOI: 10.1177/2048872617730037
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of subsequent myocardial infarction, stroke, and death in stable post-myocardial infarction patients: A nationwide cohort study

Abstract: For acute myocardial infarction patients surviving one year without subsequent events of recurrent myocardial infarction or stroke, the risk of cardiovascular events remained high. Eight predictors identified patients at increased risk for subsequent cardiovascular events within the next three years. These results suggest an unmet need, particularly in patients with additional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…This may have further shortened the mean follow‐up period in this study. Despite the higher rate of early discontinuation of DAPT, the risk of death, MI, and stroke at 1 year after AMI was not higher in a Taiwan nationwide cohort study than in a Swedish national registry study (15.1% vs. 18.3%) 37,38 . Pivotal trials of ticagrelor and prasugrel in ACS have shown greatest ischemic reduction during the first month following the treatment initiation 9,39 .…”
Section: Discussionmentioning
confidence: 95%
“…This may have further shortened the mean follow‐up period in this study. Despite the higher rate of early discontinuation of DAPT, the risk of death, MI, and stroke at 1 year after AMI was not higher in a Taiwan nationwide cohort study than in a Swedish national registry study (15.1% vs. 18.3%) 37,38 . Pivotal trials of ticagrelor and prasugrel in ACS have shown greatest ischemic reduction during the first month following the treatment initiation 9,39 .…”
Section: Discussionmentioning
confidence: 95%
“…Independent predictors of recurrent CVD events or death include age, smoking, hypertension (HTN), dyslipidemia, diabetes mellitus, chronic kidney disease, and the underutilization of medications recommended by current treatment guidelines [9, 10]. A previous study conducted in the United Arab Emirates (UAE) reported 35% with HTN, 34% having dyslipidemia, 14.4% had a history of coronary artery disease (CAD) and 29.5% with diabetes mellitus also had concomitant macrovascular complications [11].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Lewington et al links arterial hypertension to death from myocardial infarction as well as stroke in middle and old age. 55 Chen et al found arterial hypertension to be an independent risk factor for death from myocardial infarction, hypertension and prior stroke in survivors of previous myocardial infarction, 56 and Thune et al found that antecedent hypertension independently increased the risk of heart failure. 57 …”
Section: The Basis Of Chiropractic To Cardiovascular Physiologymentioning
confidence: 99%